Performance Evaluation of Rajasthan Handloom Development Corporation (RHDC) with Respect to Jaipur District - Goswami, Rachana; Jain, Ruby (Prabandhan: Indian Journal of Management, 2012)
The present study highlights the performance evaluation of services provided by the Rajasthan Handloom Development Corporation (RHDC), a state government body working for the development of handloom weavers working in clusters in Jaipur District. The sample of the study comprised of senior officials (n = 20) and beneficiaries (n = 320) of RHDC. The results show that the organization is facing a financial crunch, which has adversely affected the growth of the weavers. The cluster approach got crumpled and weavers had to merge into the cooperative fold for their survival. Thus, there is an urgent need to review the performance of the organization and work on certain strategies to develop the organization, so that successful fulfillment of the objectives, i.e. the development of the handloom sector, for which this organization was established, can be done.